Terms of service, cramped budgets, and good library citizenship: the Netflix dilemma - Harris, Colleen S. (The Bottom line (New York, N.Y.), 2010)
Purpose - The purpose of this paper is to explore the implications of libraries using Netflix to supplement their own audiovisual collections.Design methodology approach - A review of the current discussion regarding breaking terms of service is presented along with several complications that arise from libraries disregarding the Netflix terms of service agreement.Findings - The problem of providing patrons with access to materials that the library cannot afford to purchase and which cannot be acquired via interlibrary loan has no simple answer. Librarians may be in a unique position to encourage changes to terms of service that may be more friendly to lending institutions, but only if they do not squander their legitimacy by disregarding current terms.Research limitations implications - Most of the conversation is based on anecdote and recent practice. Very little has been written on how to fix this problem.Practical implications - This paper brings this issue to the forefront in an effort to engage librarians in a discussion about the ethical, practical and legal implications of breaking terms of service in the pursuit of serving patrons.Social implications - The culture of library practice could be affected by this issue, and may have wider ramifications in terms of future copyright, licensing, and terms of service agreements.Originality value - The paper is timely, addressing a current question and debate within their field. It proposes that librarians should find solutions only after seriously considering the legal, ethical, and economic implications of their actions.